THE LEARNING OF NANDO IN FACE OF TWO EXTREME SITUATIONS: THE CIVIL-MILITARY COUP AND TORTURE - Ochiussi, Glener Cruz [UNESP] (Univ Federal Santa Maria, 2018)
This work intends to analyze the learning of Nando - central character of the novel Quarup, by Antonio Callado - in face of two extreme situations: the civil-military coup of 1964 and the experience of torture. The first limit situation is directly related to the character Francisca, the great passion of the protagonist, the second one to Manuel Tropeiro, Sincere friend of Nando. In a schematic way, these two characters guide the Political formation of Nando in front of the situations mentioned above. According to our reading, these two conflicting passages of the plot are crucial for the integral formation of Nando.
Keywords: Antonio Callado; civil-military coup; Quarup; the political formation of Nando; torture